2009
DOI: 10.1021/es9014025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Carbonaceous Aerosol Concentrations in East and West Jerusalem

Abstract: Carbonaceous aerosol concentrations and sources were compared during a year long study at two sites in East and West Jerusalem that were separated by a distance of approximately 4 km. One in six day 24-h PM(2.5) elemental and organic carbon concentrations were measured, along with monthly average concentrations of particle-phase organic compound tracers for primary and secondary organic aerosol sources.Tracer compounds were used in a chemical mass balance ICMB) model to determine primary and secondary source c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(35 reference statements)
0
16
1
Order By: Relevance
“…Thus, an initial step in determining the reproducibility of this, or a similar technique, is a coordinated intercomparison study of researchers skilled in these methods. It should also be noted that other laboratories [18,47,48] have used a similar source apportionment techniques for SOA but with typically different GC-MS analysis methods (e.g., electronic ionisation vs. chemical ionisation; quadrupole MS vs. ion-trap MS). This has the potential of introducing systematic errors into the analysis when using the mass fraction values presented herein based on ketopinic acid, although the results from their analyses [18,47,48] appear very credible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an initial step in determining the reproducibility of this, or a similar technique, is a coordinated intercomparison study of researchers skilled in these methods. It should also be noted that other laboratories [18,47,48] have used a similar source apportionment techniques for SOA but with typically different GC-MS analysis methods (e.g., electronic ionisation vs. chemical ionisation; quadrupole MS vs. ion-trap MS). This has the potential of introducing systematic errors into the analysis when using the mass fraction values presented herein based on ketopinic acid, although the results from their analyses [18,47,48] appear very credible.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the main contributors were from monoterpenes transported from temperate regions of North America, although levels were generally below 1 μgC m −3 . Finally, at two East Mediterranean locations, von Schneidemesser et al [18] determined that SOC from isoprene, β-caryophyllene, and toluene comprised 1.4 μgC m −3 or about 30% of the measured OC. By contrast, studies conducted by El Haddad et al [19] found the contribution of biogenic SOC amounted to less than 5% of the organic carbon for the north Mediterranean city of Marseille during the summer of 2008.…”
Section: International Journal Of Environmental Analytical Chemistry mentioning
confidence: 99%
“…The high level of pollution due to these fires can be detected from satellites (Kaufman et al, 2006). LBO events have been studied in the past (e.g., Sarnat et al, 2010;von Schneidemsser et al, 2010), including studies of the particles' chemical aging and optical properties (e.g., Adler et al, 2011). However, no studies have been reported on the properties of these particles as IN.…”
Section: Characteristics Of the Research Areamentioning
confidence: 99%
“…The results indicated that the main contributors were from monoterpenes transported from temperate regions of North America, although levels were generally below 1 gC m Ϫ3 . Finally, at two eastern Mediterranean locations, Von Schneidemessen et al 24 determined that SOC from isoprene, ␤-caryophyllene, and toluene comprised 1.4 gC m Ϫ3 , or approximately 30% of the measured OC.…”
Section: Introductionmentioning
confidence: 99%